Emerging targeted therapies for chronic obstructive pulmonary disease: from symptom control to precision medicine - Guangwei Chen; Haishun Yang; Weihang Sun; Jiawen Shen; Fang Ma; Jinli Qin; Xianhong Wang; Yalong Liu; Na Chen; Tieshan Teng; Shichang Sun; Xinying Ji (Frontiers in Pharmacology, 2026)
Chronic obstructive pulmonary disease (COPD) is a highly prevalent chronic inflammatory disorder of the airways characterized by substantial morbidity, disability, and mortality. It poses a significant global public health burden. Conventional therapies for COPD, which mainly rely on bronchodilators and inhaled corticosteroids, effectively relieve symptoms and reduce exacerbation frequency in patients. However, their clinical utility is limited by safety concerns and heterogeneous treatment responses across disease phenotypes. Moreover, these therapeutic approaches cannot halt or reverse disease progression. With increasing understanding of the complex molecular and cellular mechanisms underlying COPD pathogenesis, therapeutic approaches are evolving from conventional symptom-oriented management toward precision medicine and mechanism-based targeted interventions. This review systematically summarizes recent advances in emerging targeted therapies for COPD, including monoclonal antibodies directed against key inflammatory pathways, small-molecule modulators targeting core pathogenic mechanisms, and stem cell-based therapies. By selectively modulating critical processes involved in chronic inflammation, tissue injury, and airway remodeling, these novel therapeutic strategies offer promising therapeutic opportunities, particularly for patients with corticosteroid resistance and frequent exacerbations.